Heroes and Legends of Fin-de-Siècle France : Gender, Politics, and National Identity. - Datta, Venita, 1961- (Cambridge University Press, 2011)
Venita Datta examines representations of fictional and real heroes in the boulevard theater and mass press during the fin de siècle.